Zeeman effect of weak La I lines investigated by the use of optogalvanic spectroscopy. (March 2017) - Sobolewski, Ł.M.; Windholz, L.; Kwela, J.
Abstract: New Landé- g J factors of 35 energy levels of La I, found from investigations of 40 spectral lines in the wavelength range 562.959÷609.537 nm, were determined. As a source of free La atoms a hollow cathode discharge lamp was used. We monitored the signal of the optogalvanic effect appearing when a laser beam is passing through the hollow cathode. Spectra were recorded in the presence of a magnetic field of about 800 G produced by a permanent magnet, for two linear polarizations of the exciting laser light. Optogalvanic spectroscopy is a very sensitive method, so we were able to observe the Zeeman effect of very weak atomic lines. In this way we have determined for the first time the Landé- g J factors for 35 recently found levels of neutral La. The Landé g J - factors for several other levels were reinvestigated. Abstract : Highlights: New metod of Lande gJ factors measurement was used for observation of La I spectra. New experimental gJ factors have been determined. Hfs data for La I levels have been tested and corrected.